The Influence of the Quick on the Draw Type Cooperative Learning Model on the Mathematics Learning Activities - Wafith Azizah; Risnawita Risnawita; Rusdi Rusdi; Tasnim Rahmat (Darul Yasin Al Sys, 2026)
Students’ mathematics learning activity is an important indicator of learning success. However, preliminary observations and interviews with teachers and students at SMKN 2 Bukittinggi indicated that students’ mathematics learning activity remained low, partly due to teacher-centered instruction and limited variation in learning models. This study aims to determine the effect of the Quick on the Draw cooperative learning model on students’ mathematics learning activities in Grade X Hospitality at SMKN 2 Bukittinggi. This research employed a quantitative approach with a pre-experimental design using the Static Group Comparison Design. The population consisted of three Grade X Hospitality classes at SMKN 2 Bukittinggi. The sample comprised students of Grade X Hospitality 2 as the experimental class and Grade X Hospitality 1 as the control class. Sampling was conducted using simple random sampling after normality, homogeneity of variance, and mean equality tests were performed on the population data. Data were collected using a questionnaire measuring students’ mathematics learning activities and analyzed using the t-test after fulfilling the prerequisite tests of normality and homogeneity. The results showed that tcount = 2.0479 exceeded ttable = 1.6741, indicating that H₀ was rejected and H₁ was accepted. This result was further supported by SPSS analysis, which produced a significance value of 0.045 at α = 0.05, showing that 0.045 < 0.05. Therefore, the study concludes that the Quick on the Draw cooperative learning model has a significant effect on students’ mathematics learning activities in Grade X Hospitality at SMKN 2 Bukittinggi in the 2025/2026 academic year. These findings contribute to mathematics education by demonstrating the potential of cooperative learning strategies to increase student participation and provide practical implications for teachers in designing more interactive and student-centered mathematics learning.